A Pre-Clinical Large Animal Model of Sustained Liver Injury and Regeneration Stimulus. Issue 1 (December 2018) - Inomata, Kenta; Tajima, Kazuki; Yagi, Hiroshi; Higashi, Hisanobu; Shimoda, Hirofumi; Matsubara, Kentaro; Hibi, Taizo; Abe, Yuta; Tsujikawa, Hanako; Kitago, Minoru; Shinoda, Masahiro; Obara, Hideaki; et al.
Abstract A feasible large animal model to evaluate regenerative medicine techniques is vital for developing clinical applications. One such appropriate model could be to use retrorsine (RS) together with partial hepatectomy (PH). Here, we have developed the first porcine model using RS and PH. RS or saline control was administered intraperitoneally to Göttingen miniature pigs twice, two weeks apart. Four weeks after the second dose, animals underwent PH. Initially, we tested different doses of RS and resection of different amounts of liver, and selected 50 mg/kg RS with 60% hepatectomy as our model for further testing. Treated animals were sacrificed 3, 10, 17 or 28 days after PH. Blood samples and resected liver were collected. Serum and liver RS content was determined by Liquid Chromatograph-tandem Mass Spectrometer. Blood analyses demonstrated liver dysfunction after PH. Liver regeneration was significantly inhibited 10 and 17 days after PH in RS-treated animals, to the extent of 20%. Histological examination indicated hepatic injury and regenerative responses after PH. Immunohistochemical staining demonstrated accumulation of Cyclin D1 and suppression of Ki-67 and PCNA in RS-treated animals. We report the development of the first large animal model of sustained liver injury with suppression of hepatic regeneration.